Pretrial Diversion in the 21st century - (:unkn) unknown (My University, 2016)
This monograph highlights ndings from a national survey of pretrial diversion programs conducted by the National Association of Pretrial Services Agencies (NAPSA). !e survey is intended to increase knowledge about diversion programs, create a comprehensive national directory of these programs, and promote networking, cooperation and sharing of technical expertise. It is the rst comprehensive survey of pretrial diversion programs since 1982.